Broadband dielectric resonator antenna with dual‐frequency circularly polarized response for WLAN and WiMAX applications. (5th October 2021) - Sharma, Anand; Dwivedi, Ajay Kumar; Narayaswamy, Nagesh Kallollu; Gupta, Ashish; Tripathi, Devendra Kumar
Abstract: In this paper, a moon‐shaped aperture‐coupled ring‐shaped dielectric resonator antenna (DRA) is suggested, realized, and tested. The L‐shaped microstrip line is designed to stimulate the aperture. Vital characteristics of the proposed radiator are as follows: (a) Broadband DRA with dual‐frequency circular polarized (CP) response is realized by the mixture of HEM 11 δ X and HEM 11 δ Y mode in‐ring DRA; (b) wide impedance bandwidth is attained with the help of dropping the effective permittivity of radiating structure by converting cylindrical shape into a ring shape. To test the practical feasibility, the proposed antenna design is fabricated and tested inside the anechoic chamber. Practical outcomes confirm that the proposed antenna works over the frequency range of 2.44–3.66 GHz along with supporting dual CP waves within the operating range, i.e., 2.44–2.64 and 3.4–3.65 GHz respectively. Broadsided (θ = 0 0 and ϕ = 0 0 ) RHCP radiation pattern makes the proposed antenna design applicable for IEEE 802.15.4 wireless sensor network (2.5 GHz) and WiMAX (3.5 GHz). Abstract : In this paper, a moon‐shaped aperture‐coupled ring‐shaped dielectric resonator antenna is realized, and tested. The L‐shaped microstrip line is designed to stimulate the aperture. Vital characteristics are as follows: (a) CP response is realized by the mixture of HEM 11 δ X and HEM 11 δ Y mode. Proposed antenna is applicable for IEEE 802.15.4 WSN (2.5 GHz) and WiMAX (3.5 GHz).